Nilai Lingkungan dalam Kumpulan Cerpen Pilanggur Salusin Kisdap Banjar Karya Hatmiati Masy’ud - Nurhidayati Kurniasih (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2020)
Penelitian ini bertujuan mendeskripsikan kearifan lingkungan dalam kumpulan cerpen Pilanggur Salusin Kisdap Banjar karya Hatmiati Masy’ud yang diwakili oleh Palak (Asap), Tambun (Hantu Banyu), dan Tulak Bala (Tolak Bencana). Teori ekokritik dan teori sosiologi digunakan dalam penelitian ini sebagai alat untuk menganalisis karya sastra dari sudut pandang lingkungan dan menghubungkannya dengan fakta sosial yang diacunya. Metode penelitian ini adalah metode deskriptif kualitatif sedang teknik pengumpulan datanya menggunakan teknik simak, teknik catat, dan teknik kepustakaan. Prosedurnya membaca secara cermat; meneliti masalah kearifan lingkungan; mengklasifikasikan dan mengalisis permasalahan lingkungan berdasarkan pendekatan sosiologi karya sastra dalam teori sosiologi sastra dan teori ekokritik kemudian menyimpulkan kearifan lingkungan dalam cerpen pilihan tersebut adalah (1) penghargaan alam; (2) masalah lingkungan alam; dan (3) kearifan lokal dalam mengatasinya.This study is motivated by the increasing issue of global environmental warming. This study aims to describe environmental value in the short story collection of Pilanggur Salusin Kisdap Banjar by Hatmiati Masy’ud. This study uses descriptive qualitative method. The data are in the form of sentences containing environmental value in the short story collection of Pilanggur, they are; (1) Palak (smoke), (2) Tambun (Water Ghost), (3) Tulak Bala. The data technique used in this study is reading, note-taking, and library technique. The data analysis is done through several stages, they are (1) reading carefully, (2) identifying the problem, (3) classifying the environmental value, (4) analyzing the problem of environmental value based on extrinsic approach in sociology literature theory and ecology theory, (5) summarizing the environmental value about the solution offered in the story. The result shows that there are environmental values with its conflict and solutions offered, they are; (1) Palak short story, the conflict is about prolonged smoke pollution and environmental value with its offered solution, they are from action and spiritual aspect, (2) Tambun short story, the conflict is about polluted and dirty river and the solution is by maintaining the existence of the river, (3) Tulak Bala short story, the conflict is about village fire and the solution is by raising the knowledge of the people about the importance of environmental awareness. Afterward, ecocriticism in the short story collection of Pilanggur Salusin Kisdap Banjar are (1) the representation of nature in the short story, (2) the role of physical background (environment) in the plot of the short story, (3) the values of local wisdom, and (4) the metaphor of land (earth) and its attitudes.